2009
DOI: 10.1016/s1130-1473(09)70197-6
|View full text |Cite
|
Sign up to set email alerts
|

Hemorrhagic stroke with intraventricular extension in the setting of acute posterior reversible encephalopathy syndrome (PRES): Case report

Abstract: SummaryWe report the case of an eighteen year-old pregnant female with preeclampsia and florid signs and symptoms of posterior reversible encephalopathy syndrome (PRES) in whom intracerebral hemorrhage was evidenced following delivery. Management included blood pressure control, external ventricular drainage and lumboperitoneal shunt. To our knowledge this is the first report of intracranial hemorrhage occurring concurrently with peripartum acute PRES. This case was successfully treated with good outcome upon … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…The patient required ventriculostomy for increased intracranial pressure. 5 Although subarachnoid hemorrhage associated with posterior reversible encephalopathy syndrome has been reported in the literature, there is no prior report of intraventricular hemorrhage with associated subarachnoid hemorrhage. In a review of 23 patients with intracranial hemorrhage associated with posterior reversible encephalopathy syndrome by Hefzy et al, 7 patients were identified with subarachnoid hemorrhage and 2 patients with combined subarachnoid hemorrhage and parenchymal hemorrhage.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The patient required ventriculostomy for increased intracranial pressure. 5 Although subarachnoid hemorrhage associated with posterior reversible encephalopathy syndrome has been reported in the literature, there is no prior report of intraventricular hemorrhage with associated subarachnoid hemorrhage. In a review of 23 patients with intracranial hemorrhage associated with posterior reversible encephalopathy syndrome by Hefzy et al, 7 patients were identified with subarachnoid hemorrhage and 2 patients with combined subarachnoid hemorrhage and parenchymal hemorrhage.…”
Section: Discussionmentioning
confidence: 99%
“…Only 2 cases of intraventricular hemorrhage complicating a posterior reversible encephalopathy syndrome presentation have been reported. 4,5 Aranas et al described a 56-year-old man 5 months status after liver transplantation on tacrolimus admitted for elevated liver function tests. Four days later, he developed encephalopathy and coma.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As the name suggests, manifestations of PRES are usually transient and complete recovery is the rule. Most cases of PRES reported in the obstetric literature involve postpartum patients, with only a few cases of antepartum PRES [1][2][3][4] . We report a primigravid woman who presented with an abrupt onset of eclampsia and PRES.…”
mentioning
confidence: 99%